This is the Equation: 2x + 6
we do 2x-1/y=w+2/2z
2x-1/y we multiple each side y
2x-1/y×y=2x-1
then w+2/2z
we said×2z×2z
then we got
w+2
later
2x-1=w+2=
then 1 become another side
which is 1+2=3
then
w=3-2x
I hope it's correct
A number is randomly selected from ">{1, 2, 3, 4, 5, 6, 7, 8, 9, 10}{1, 2, 3, 4, 5, 6, 7, 8, 9, 10}{1, 2, 3, 4, 5, 6, 7, 8, 9
Oduvanchick [21]
Answer:
Sry im not sure what this means pls explain a bit more
Step-by-step explanation:
(2x - 6) - (10x - 7) # Starting expression
-8x - 1 # Combine like terms
Final answer:
-8x - 1
Hope this helps!